Efektivitas Program Promosi dalam Meningkatkan Minat Kunjung Perpustakaan di SDN 32 Bungo Pasang - Muhammad Habib Ramadhan (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the effectiveness of the promotion program in increasing the interest in visiting the library at SDN 32 Bungo Pasang. The background of this study is based on how effective the library promotion program is in increasing the interest in visiting the information system that is able to provide convenience, speed, and efficiency in searching and managing library collections in the digital era. The method used is quantitative descriptive. The results of the study indicate that the effectiveness of the promotion program in increasing the interest in visiting the library at SDN 32 Bungo Pasang is in the very good category, with an average score of 3.36 on an interval scale of 3.28–4.03. These findings indicate that the promotion program has helped increase the interest in visiting the library, making it easier for students to find books in the collection, and increasing student satisfaction and experience in obtaining information. Thus, the library promotion program at SDN 32 Bungo Pasang is considered effective in supporting the improvement of the accessibility of collection data and the quality of library services.